Perancangan Interior NBL Center di Surabaya - Husin, Ivanna BJ (Intra, 2015)
NBL Center is a place providing facilities in education and other facilities. Various facilities offered gallery, theater, cafe, and so many more. Surabaya, has so many basketball lover, but the lack of a facility makes the basketball lover hard to get into them. For lack of adequate facilities, and education facilities for youth basketball in surabaya.In the first phase and will use some methods. One thing that is required as data field that includes the physical and non-physical associated with estates although the progress relating to the end user, Typlogy comparison of the literary theories and other data to design basketball center. The data will be continued with a sketch of the concept.And you will find the final design.